2005
DOI: 10.1042/bj20042067
|View full text |Cite
|
Sign up to set email alerts
|

An abortive apoptotic pathway induced by singlet oxygen is due to the suppression of caspase activation

Abstract: Singlet oxygen causes the cytotoxic process of tumour cells in photodynamic therapy. The mechanism by which singlet oxygen damages cells is, however, not fully understood. To address this issue, we synthesized and used two types of endoperoxides, MNPE (1-methylnaphthalene-4-propionate endoperoxide) and NDPE (naphthalene-1,4-dipropionate endoperoxide), that generate defined amounts of singlet oxygen at 37 degrees C with similar half lives. MNPE, which is more hydrophobic than NDPE, induced the release of cytoch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 54 publications
1
30
0
Order By: Relevance
“…RBL cells are sensitive to glucosylating toxins and are a well-established cell line for studying apoptotic cell death; furthermore, RBL cells can be synchronized using the thymidine double-block technique (20,35,36,42). RBL cells were cultured in minimum essential medium supplemented with 15% heat-inactivated fetal calf serum, 100 g/ml penicillin, 100 U/ml streptomycin, and 1 mM sodium pyruvate.…”
Section: Methodsmentioning
confidence: 99%
“…RBL cells are sensitive to glucosylating toxins and are a well-established cell line for studying apoptotic cell death; furthermore, RBL cells can be synchronized using the thymidine double-block technique (20,35,36,42). RBL cells were cultured in minimum essential medium supplemented with 15% heat-inactivated fetal calf serum, 100 g/ml penicillin, 100 U/ml streptomycin, and 1 mM sodium pyruvate.…”
Section: Methodsmentioning
confidence: 99%
“…We have recently shown that the cell death induced by singlet oxygen is atypical to apoptosis [18]. This is due to the suppression of the caspase cascade prior to apoptosome formation and the direct inhibition of caspase activity and the proapoptotic function of cytochrome c by singlet oxygen [18,19]. Despite extensive study, however, we were unable to identify the amino acid modification responsible for this, probably because of the complex nature of the oxidation products.…”
Section: Discussionmentioning
confidence: 38%
“…At the initial stage of apoptosis after the stimuli, cytochrome c is generally released from mitochondria and activates apoptosome formation, leading to the activation of the caspase cascade. We have recently shown that the cell death induced by singlet oxygen is atypical to apoptosis [18]. This is due to the suppression of the caspase cascade prior to apoptosome formation and the direct inhibition of caspase activity and the proapoptotic function of cytochrome c by singlet oxygen [18,19].…”
Section: Discussionmentioning
confidence: 99%
“…involves excitation of the photosensitizer with light, but energy is transferred in this case to the triplet ground state of molecular oxygen, resulting in excited singlet state oxygen which is highly cytotoxic (Otsu K et al, 2005). In type I mechanism, oxygen is not always necessary for the photodynamic action to take place; however, in type II mechanism, oxygen is essential.…”
Section: Introductionmentioning
confidence: 99%